Social housing: an aesthetic analysis - Reis, Antônio Tarcísio da Luz (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
This paper explores internal and external aesthetic aspects in 12 housing estates, in the metropolitan region of Porto Alegre. The image and appearance of housing estates and visual composition of buildings, and how the aesthetic aspects affect resident attitudes and behavior concerning the housing environment, are investigated, as well as the impact of some household characteristics on feelings about the aesthetics of housing estates. Data was collected through questionnaires, applied to 374 housing units, structured interviews, physical measurements, and observations of behavior and physical traces. Data analysis was carried out qualitatively and quantitatively, by means of non-parametric statistical tests, such as Kruskal-Wallis and Spearman rank correlation. Results show that aspects associated with the maintenance of dwelling facades dominate the explanations for the external aesthetics being considered satisfactory, while aspects associated with the maintenance of facades together with those associated with visual composition of the facades lead the explanations of those who consider the external aesthetics dissatisfactory. Additionally, it appears that the adopted approach constituted by three levels of aesthetic experience, visual composition, appearance and image, may help to understand the different nature of aesthetics aspects in social housing.